(untitled) (Conference on English Language Teaching, 2025)
Recently, the world has seen an enormous improvement in technology, particularly the application of Artificial Intelligence (AI). It has rapidly transformed the way individuals, organisations, and societies operate. As engagement with AI becomes increasingly pervasive across sectors such as education, healthcare, industry, and communication, it brings forth a dual landscape of unprecedented opportunities and complex challenges. This paper describes the dynamic interactions between humans and AI systems, focusing on the benefits of enhanced efficiency, personalisation, and innovation, while also addressing critical concerns including ethical dilemmas, data privacy, algorithmic bias, and the displacement of human labour. By describing the current trends and future projections, this article provides a balanced perspective on how stakeholders can navigate the evolving AI ecosystem responsibly and effectively. Finally, this discussion aims to inform policymaking, guide educational frameworks, and empower users to engage critically and constructively with AI technologies.